New directions in social theory : race, gender and the canon - Reed, Kate, 1972- (SAGE, 2006)
'Beyond Social Theory' offers a passionate contribution to the debate about social theory & its role, using as a medium a discussion of the ways in which gender & race have contributed to the exclusion of important thinkers from the sociological canon.